Leadership Challenges in Nigeria, Africa, and Globally: Tantangan Kepemimpinan di Nigeria, Afrika, dan Global - Nura Umar Manya Manya (SiRad: Pelita Wawasan, 2026)
Leadership remains one of the most critical determinants of governance effectiveness, institutional performance, and sustainable development across the world. Despite numerous political and administrative reforms, many countries continue to experience persistent challenges associated with corruption, weak institutions, economic instability, technological disruption, insecurity, and declining public trust. This study examined leadership challenges in Nigeria, Africa, and the global community within the context of 2026. Adopting a comparative qualitative research design, the study relied on secondary data obtained from scholarly literature, policy documents, and reports from international organizations such as the United Nations, International Monetary Fund, World Bank, and African Union. The analysis was guided by transformational leadership theory and institutional theory. Findings revealed that global leadership is increasingly challenged by artificial intelligence, climate change, economic uncertainty, and democratic polarization. In Africa, leadership effectiveness continues to be constrained by institutional fragility, economic dependency, and governance deficits. Specifically in Nigeria, persistent issues such as corruption, prebendal politics, ethno-religious divisions, youth exclusion, and weak public institutions remain significant barriers. The study concludes that meaningful progress requires a combination of transformational leadership, institutional strengthening, merit-based political recruitment, and active citizen participation. [Kepemimpinan tetap menjadi salah satu penentu paling kritis terhadap efektivitas pemerintahan, kinerja institusional, dan pembangunan berkelanjutan di seluruh dunia. Terlepas dari berbagai reformasi politik dan administratif, banyak negara terus mengalami tantangan yang berkaitan dengan korupsi, institusi yang lemah, ketidakstabilan ekonomi, disrupsi teknologi, ketidakamanan, dan menurunnya kepercayaan publik. Studi ini menelaah tantangan kepemimpinan di Nigeria, Afrika, dan komunitas global dalam konteks tahun 2026. Dengan mengadopsi desain penelitian kualitatif komparatif, studi ini mengandalkan data sekunder yang diperoleh dari literatur ilmiah, dokumen kebijakan, serta laporan dari organisasi internasional seperti Perserikatan Bangsa-Bangsa, Dana Moneter Internasional, Bank Dunia, dan Uni Afrika. Analisis ini dipandu oleh teori kepemimpinan transformasional dan teori institusional. Temuan menunjukkan bahwa kepemimpinan global semakin ditantang oleh kecerdasan buatan, perubahan iklim, ketidakpastian ekonomi, dan polarisasi demokrasi. Di Afrika, efektivitas kepemimpinan terus dibatasi oleh kerapuhan institusional, ketergantungan ekonomi, dan defisit pemerintahan. Secara khusus di Nigeria, masalah persisten seperti korupsi, politik prebendal, perpecahan etno-religius, eksklusi pemuda, dan institusi publik yang lemah tetap menjadi hambatan signifikan. Studi ini menyimpulkan bahwa kemajuan yang bermakna membutuhkan kombinasi kepemimpinan transformasional, penguatan institusi, rekrutmen politik berbasis prestasi, dan partisipasi warga yang aktif. ]